Neuropsychological functions and visual contrast sensitivity in schizophrenia: the potential impact of comorbid posttraumatic stress disorder (PTSD) - Halasz, Ibolya; Levy-Gigi, Einat; Kelemen, Oguz; Benedek, Gyorgy; Kéri, Szabolcs (Frontiers in Psychology, 2013)
Previous studies have revealed a high prevalence of posttraumatic stress disorder (PTSD) in patients with other severe mental disorders, including schizophrenia. However, the neuropsychological and psychophysical correlates of comorbid PTSD are less exactly defined. The purpose of the present study was to assess immediate and delayed memory, attention, visuospatial skills, language, and basic visual information processing in patients with schizophrenia with or without PTSD. We recruited 125 patients with schizophrenia and 70 healthy controls matched for visual acuity, age, gender, education, and socioeconomic status. Twenty-one of patients with schizophrenia exhibited comorbid PTSD. We administered the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and visual contrast sensitivity tasks for low spatial/high temporal frequency (0.3 cycle/degree and 18 Hz) and high spatial/low temporal frequency (10 cycles/degree and 1Hz) sinusoidal gratings. All patients were clinically stable and received antipsychotic medications. Results revealed that relative to healthy controls, patients with schizophrenia exhibited significant and generalized neuropsychological dysfunctions and reduced visual contrast sensitivity, which was more pronounced at low spatial/high temporal frequency. When we compared schizophrenia patients with and without PTSD, we found that patients with comorbid PTSD displayed lower scores for RBANS attention, immediate and delayed memory, and visuospatial scores. Schizophrenia patients with or without PTSD displayed similar visual contrast sensitivity. In conclusion, comorbid PTSD in schizophrenia may be associated with worse neuropsychological functions, whereas it does not affect basic visual information processing.